A DBN-based reliability analysis method for ship standby system considering time redundancy - Cao, Enze; Long, Zhendong; Ma, Ying; Huang, Yuanxing; Liang, Xiaofeng (Ocean engineering, 2025)
As ship performance and functionality continue to advance, ship systems are becoming increasingly complex. To enhance the reliability of these complex systems, redundant backup is commonly implemented for critical systems. Additionally, due to the extended mission duration of ships, time redundancy is often incorporated to allow for repair of malfunctioning equipment within typical mission profiles. The presence of dynamic problems resulting from redundant backup and time redundancy brings difficulty for ship reliability analysis and evaluation. This paper presents a reliability analysis method for ship standby systems that considers time redundancy to address this problem. Leveraging the characteristic features of standby systems, this study focuses on the dynamic transfer mechanism of the standby system to incorporate the trait of time redundancy into the reliability evaluation model. Specifically, a reliability model for standby system is constructed using a Dynamic Bayesian network (DBN) to analyze the effect of time redundancy on standby system reliability with different parameters. The reliability analysis of a ship power system demonstrated that the proposed method effectively captures the dynamic characteristic of redundant backup and time redundancy, providing valuable guidance for actual application in ship reliability engineering. •Reliability analysis model for standby systems with time redundancy based on DBN.•Time slice length is reanalyzed to obtain CPT of DBN node.•DBN models are developed for cold and warm spare system.•Impact of time redundancy on ship power system is studied by proposed method.